Manipulating Mammal Herbivory in South Patagonia Forests: Effects on Plant Species Assemblage, Survival and Short-Term Growth Response of Nothofagus antarctica Seedlings - Soler, Rosina; Bustamante, Gimena Noemi; Blazina, Ana Paula (Proceedings of The 1st International Electronic Conference on Forests — Forests for a Better Future: Sustainability, Innovation, Interdisciplinarity)
Livestock browsing and large wild herbivores in forested areas have been perceived as conflicting with silviculture and forest conservation for long time. However, silvopastoral systems in native forests entail livestock manipulation in space and time, to reduce negative impacts on forest structure and dynamics. In 2014, we established eight 15×15m fences (and the respective control plots with browsing) in four Nothofagus antarctica (ñire) silvopastoral sites in Tierra del Fuego Island, to protect tree seedlings and vegetation from cattle and guanaco browsing. After five growing seasons, the exclusion treatment favored regeneration of ñire by reducing browsing pressure while increasing seedling growth rate, though the effect on seedling survival was weak. Soil moisture increased while soil compaction decreased over years in all fields, though the fences effect was weak. Palatable forbs (e.g., Taraxacum sp., Osmorhiza sp.) and grasses (e.g., Agrostis sp., Bromus unioloides) increased much more in abundance and height than ñire seedlings within fences. Thus, the use of exclusion treatments to manipulate browsing impact enhance short-term growth of ñire regeneration in south Patagonia forests used for cattle production. However, a negative effect by competing understory vegetation in fences probably also occur in the long term. Fil: Soler, Rosina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Bustamante, Gimena Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Blazina, Ana Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina 1st International Electronic Conference on Forests Basilea Suiza Multidisciplinary Digital Publishing Institute